Anti-falling shell of electronic equipment
By using polymer polymer substrates and composite materials of TPU and aramid fibers in the shell of electronic equipment, combined with impact modifiers, the problem of insufficient drop resistance in the shell in the existing technology is solved, and high toughness is achieved and the improvement of impact resistance ensures the safety and user experience of the equipment.
Patent Information
- Application Number
- CN202411255027.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-09
AI Technical Summary
Existing electronic equipment shells have shortcomings in their anti-fall performance, especially plastic shells have poor impact resistance, are prone to cracking, and may deform or brittle at extreme temperatures, resulting in reduced safety and durability.
Using polymer polymer substrates (such as PCs) with composite materials of TPU and aramid fibers, the rubber elastomer of TPU and reinforced fillers of aramid fibers are combined with impact modifiers, thermal stabilizers, antioxidants and Lubricant, forming an electronic device housing with high toughness and impact resistance. TPU absorbs energy during impact, and aramid fibers enhance the mechanical properties of the material through modification treatment, ensuring that the shell can effectively absorb and disperse impact forces when it falls or impacts.
It significantly improves the anti-fall performance of the electronic device shell, reduces damage to internal components, extends the service life of the device, while maintaining lightness, and improving user safety and trust.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of electronic equipment and discloses an anti-fall shell of an electronic equipment. Background Art
[0002] Electronic devices have gradually occupied every aspect of people's daily life. However, electronic devices, especially mobile electronic devices, such as charging plugs, power banks, portable projectors, wireless headphones, smart watches, game consoles, portable media players, etc., will inevitably suffer physical damage such as falling and collision during use.
[0003] Existing electronic device shells are mostly made of plastic, metal or alloy materials. Although these materials can protect the internal battery and circuit board to a certain extent, they have obvious deficiencies in drop resistance. Although metal or alloy shells have a strong structure, they are heavy and may produce a large impact force on internal components when they fall. Although plastic shells are light, they have poor impact resistance and are easy to break when they fall; in addition, these materials may deform and become brittle under extreme temperatures, further reducing the safety and durability of electronic devices.
[0004] Since electronic devices contain lithium batteries and other sensitive electronic components, once the casing is damaged in a fall or collision, it may not only cause battery leakage, short circuit or even fire and explosion, but also cause the loss of user personal information. Therefore, improving the drop resistance of electronic device casings is crucial to ensure the personal safety and data security of users. An electronic device casing with excellent drop resistance can effectively absorb and disperse the impact force during a fall, reduce damage to internal components, extend the service life of the device, and also improve user trust and satisfaction with the product.
[0005] In summary, developing an electronic device casing that is both lightweight and highly drop-resistant is of great significance for improving the overall safety and user experience of electronic devices. Summary of the invention
[0006] In view of the problem that electronic device casings made of traditional plastic materials in the prior art have poor impact resistance and are easily broken, one of the purposes of the present invention is to provide an electronic device casing that is resistant to falling.
[0007] The present invention is implemented by the following technical solution: an anti-fall shell of an electronic device, comprising the following components by weight:
[0008] 70-85 parts of high molecular polymer substrate;
[0009] 10-15 parts of reinforcing filler;
[0010] 5-10 parts of impact modifier;
[0011] Heat stabilizer 0.1-0.5 parts;
[0012] Antioxidant 0.1-0.5 parts;
[0013] 0.5-1 part of lubricant.
[0014] As a preferred embodiment of the above technical solution, the high molecular polymer substrate is PC; and the impact modifier is TPU.
[0015] TPU, thermoplastic polyurethane, is a rubber elastomer that forms a tiny dispersed phase in the PC substrate system. The large amount of TPU dispersed phase in this system becomes a stress concentration point, absorbing and dispersing impact energy. When the molded electronic device housing is impacted by external force, TPU particles can cause tiny cracks and shear bands in the surrounding resin, absorb energy through the formation and branching of silver streaks and shear bands, and prevent further expansion of cracks, thereby reducing the risk of electronic device housing being broken and improving the impact resistance of electronic device housing.
[0016] As a preferred embodiment of the above technical solution, the antioxidant is a hindered phenol antioxidant, specifically one or more of antioxidant 1010, antioxidant 1076, and antioxidant 2246; the heat stabilizer is an organic phosphate heat stabilizer, specifically one or more of triphenyl phosphite, triisooctyl phosphite, and trinonylphenyl phosphite; and the lubricant is a stearate lubricant.
[0017] As a preferred embodiment of the above technical solution, the reinforcing filler is aramid fiber.
[0018] Aramid fibers (such as Twaron and Kevlar) can enhance the mechanical properties of polymer substrates, especially toughness, and aramid fibers have relatively low cost and good compatibility, making them compatible with high-performance and budget-constrained application scenarios.
[0019] As a preferred embodiment of the above technical solution, the aspect ratio of the aramid fiber is between 10: 1 and 20: 1. A long aspect ratio can improve the strength and modulus of the material, but an excessively long aspect ratio will lead to uneven dispersion of the aramid fiber in the system and difficulty in processing. The aspect ratio is preferably between 10: 1 and 20: 1, and the aramid fiber has a good reinforcement effect.
[0020] As a preferred embodiment of the above technical solution, the average particle size of the aramid fiber is between 10 and 20 microns. Aramid fibers with a particle size within this range can be fully dispersed in the system to provide a uniform reinforcement effect, while avoiding stress concentration and material defects caused by large particle size aramid fibers.
[0021] As a preferred embodiment of the above technical solution, the aramid fiber needs to be modified, and the modification step includes placing the aramid fiber in a 1.5-3.5 mg / ml polydopamine buffer solution and continuously stirring the reaction for 22-26 hours; then drying the aramid fiber coated with polydopamine at room temperature for 24 hours, and then immersing it in a 1.5-2.5wt% γ-aminopropyltriethoxysilane (silane coupling agent KH550) solution for 22-26 hours to obtain modified aramid fiber.
[0022] By pre-treating the aramid fiber and coating the surface of the aramid fiber with a layer of polydopamine (PDA), relevant functional hydroxyl groups are introduced to provide abundant reactive sites, enhancing the compatibility and adhesion between the fiber and PC. At the same time, the drying process can increase the adhesion stability of the PDA coating, making it less likely to fall off in subsequent steps. The KH550 molecules fully contact the hydroxyl groups on the surface of the PDA and form covalent bonds, enhancing the interfacial bonding between the aramid fiber and the PC resin, thereby significantly improving the overall performance of the PC material.
[0023] As a preferred embodiment of the above technical solution, the buffer used in the polydopamine buffer solution is 1 mol / L tris(hydroxymethyl)aminomethane hydrochloride buffer, and the pH value of the buffer is 8.5.
[0024] A second object of the present invention is to provide a method for preparing an anti-fall casing of an electronic device, comprising the following steps:
[0025] Step S1: drying the polymer substrate and reinforcing filler, and keeping the humidity of the polymer substrate and reinforcing filler after drying less than 0.04%;
[0026] Step S2: After the drying process in step S1 is completed, the high molecular polymer substrate, reinforcing filler and impact modifier, thermal stabilizer, antioxidant, and lubricant are mixed in proportion, and then melt-mixed by a twin-screw extruder to ensure that the components are evenly dispersed;
[0027] Step S3: using an injection molding process to inject molten plastic into a mold to form the shape of an electronic device housing;
[0028] Step S4: Perform post-processing such as grinding, spraying or laser engraving on the shell as needed.
[0029] In step S1, the drying process is carried out under the following conditions: maintaining the temperature within the range of 90° C. to 110° C. and continuing the drying process for 2 to 4 hours.
[0030] Beneficial effects:
[0031] The formula and preparation process adopted by the present invention can be used to form electronic device casings made of various plastic materials, including charging plugs, power banks, portable projectors, wireless headphones, smart watches, game consoles, portable media players, portable printers, solar chargers, etc.
[0032] The electronic device housing of the present invention uses thermoplastic polyurethane (TPU) and aramid fiber to compound with PC, which significantly improves the overall toughness and wear resistance of the material system. The addition of TPU enables the PC material to better absorb impact energy and reduce damage when it is subjected to collisions and falls that may occur in daily use. At the same time, the high-strength characteristics of aramid fiber provide additional impact resistance for the electronic device housing, especially the modified aramid fiber, which has a systematic improvement in the mechanical properties of the electronic device housing, including tensile strength, bending strength, notched impact strength, etc., ensuring the safety of internal components while maintaining the lightness of the electronic device. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] An anti-fall shell for an electronic device comprises the following components in parts by weight:
[0035] PC70-85 copies;
[0036] Aramid fiber 10-15 parts;
[0037] TPU 5-10 parts;
[0038] 0.1-0.5 parts of organic phosphate heat stabilizer;
[0039] Hindered phenol antioxidant 0.1-0.5 parts;
[0040] Stearate lubricant 0.5-1 part.
[0041] Specifically, the hindered phenol antioxidant may be one or more of antioxidant 1010, antioxidant 1076, and antioxidant 2246.
[0042] The organic phosphate heat stabilizer may specifically be one or more of triphenyl phosphite, triisooctyl phosphite, trinonylphenyl phosphite and the like.
[0043] The lubricant is a stearate lubricant.
[0044] The aspect ratio of aramid fibers is between 10:1 and 20:1, and the average particle size is between 10 and 20 microns.
[0045] The aramid fiber needs to be modified, and the modification process includes placing the aramid fiber in a 1.5-3.5 mg / ml polydopamine buffer solution, stirring and reacting for 22-26 hours; the buffer used in the polydopamine buffer solution is 1 mol / L tris(hydroxymethyl)aminomethane hydrochloride buffer, and the pH value of the buffer is 8.5. Then, the aramid fiber with the polydopamine coating is dried at room temperature for 24 hours, and then immersed in a solution of 1.5-2.5wt% γ-aminopropyltriethoxysilane (silane coupling agent KH550) for 22-26 hours to obtain the modified aramid fiber.
[0046] A method for preparing an anti-drop shell of an electronic device comprises the following steps:
[0047] Step S1: drying the PC, aramid fiber / modified aramid fiber, and keeping the humidity of the dried PC, aramid fiber / modified aramid fiber less than 0.04%; the drying conditions are: keeping the temperature within the range of 90°C-110°C, and continuing drying for 2-4 hours.
[0048] Step S2: Mix the PC, aramid fiber / modified aramid fiber, TPU, heat stabilizer, antioxidant, and lubricant obtained by step S1 according to a certain proportion, and then melt-mix them through a twin-screw extruder to ensure that the components are evenly dispersed.
[0049] Step S3: using an injection molding process to inject molten plastic into a mold to form the shape of an electronic device housing;
[0050] Step S4: Perform post-processing such as grinding, spraying or laser engraving on the shell as needed.
[0051] The following is an explanation of the embodiments.
[0052] The raw materials used in the embodiments of the present invention can all be purchased directly from the market.
[0053] The polymer substrate PC used in this embodiment has a density of 1.18-1.22 g / cm 3 The heat deformation temperature is 135℃ and the linear expansion coefficient is 3.8×10^-5cm / ℃. TPU uses polyester or polyether diol soft segment with an average molecular weight of 2000.
[0054] The power bank shell mold was used to form the power bank shell to verify the formula and process of the present invention. The specific embodiments are as follows.
[0055] Example 1
[0056] The raw materials and proportions of the present embodiment are as follows:
[0057] 70 parts of PC, 13 parts of aramid fiber, 8 parts of TPU, 0.5 parts of organic phosphate heat stabilizer, 0.3 parts of hindered phenol antioxidant, and 0.5 parts of stearate lubricant.
[0058] Among them, the hindered phenol antioxidant is antioxidant 1010.
[0059] The organic phosphate heat stabilizer is triisooctyl phosphite.
[0060] The lubricant may be any stearate lubricant.
[0061] The aspect ratio of aramid fiber is 10:1 and the average particle size is 10 microns.
[0062] In this embodiment, the aramid fiber is not modified.
[0063] The preparation method is as follows:
[0064] Step S1: drying the PC and aramid fibers. The drying conditions are: maintaining the temperature within the range of 90°C-110°C for 4 hours. Maintaining the humidity of the dried PC, aramid fibers / modified aramid fibers to be less than 0.04%;
[0065] Step S2: After the PC and aramid fiber dried in step S1 are mixed with TPU, heat stabilizer, antioxidant, lubricant, etc. in proportion, melt-mixed by a twin-screw extruder to ensure that the components are evenly dispersed;
[0066] Step S3: using an injection molding process to inject molten plastic into a mold to form the shape of an electronic device housing;
[0067] Step S4: performing post-processing such as grinding, spraying or laser engraving on the housing as required to form the housing of the electronic device.
[0068] Example 2
[0069] The raw materials and proportions of the present embodiment are as follows:
[0070] 80 parts of PC, 10 parts of aramid fiber, 10 parts of TPU, 0.1 parts of organic phosphate heat stabilizer, 0.5 parts of hindered phenol antioxidant, and 1 part of stearate lubricant.
[0071] Among them, antioxidant 1076 is selected as the hindered phenol antioxidant.
[0072] The organic phosphate heat stabilizer is triphenyl phosphite.
[0073] The lubricant may be any stearate lubricant.
[0074] The aspect ratio of aramid fiber is 10:1 and the average particle size is 10 microns.
[0075] In this embodiment, the aramid fiber is not modified.
[0076] The preparation method is as follows:
[0077] Step S1: drying the PC and aramid fibers. The drying conditions are: maintaining the temperature within the range of 90°C-110°C for 3 hours. Maintaining the humidity of the dried PC, aramid fibers / modified aramid fibers to be less than 0.04%;
[0078] Step S2: After the PC and aramid fiber dried in step S1 are mixed with TPU, heat stabilizer, antioxidant, lubricant, etc. in proportion, melt-mixed by a twin-screw extruder to ensure that the components are evenly dispersed;
[0079] Step S3: using an injection molding process to inject molten plastic into a mold to form the shape of an electronic device housing;
[0080] Step S4: performing post-processing such as grinding, spraying or laser engraving on the housing as required to form the housing of the electronic device.
[0081] Example 3
[0082] The raw materials and proportions of the present embodiment are as follows:
[0083] 80 parts of PC, 10 parts of aramid fiber, 10 parts of TPU, 0.1 parts of organic phosphate heat stabilizer, 0.5 parts of hindered phenol antioxidant, and 1 part of stearate lubricant.
[0084] The hindered phenol antioxidant is selected from antioxidant 1076 and antioxidant 2246 mixed in a ratio of 1:1.
[0085] The organic phosphate heat stabilizer is trinonylphenyl phosphite.
[0086] The lubricant may be any stearate lubricant.
[0087] The aspect ratio of aramid fiber is 10:1 and the average particle size is 10 microns.
[0088] In this embodiment, the aramid fiber is not modified.
[0089] The preparation method is as follows:
[0090] Step S1: drying the PC and aramid fibers. The drying conditions are: maintaining the temperature within the range of 90°C-110°C for 3 hours. Maintaining the humidity of the dried PC, aramid fibers / modified aramid fibers to be less than 0.04%;
[0091] Step S2: After the PC and aramid fiber dried in step S1 are mixed with TPU, heat stabilizer, antioxidant, lubricant, etc. in proportion, melt-mixed by a twin-screw extruder to ensure that the components are evenly dispersed;
[0092] Step S3: using an injection molding process to inject molten plastic into a mold to form the shape of an electronic device housing;
[0093] Step S4: performing post-processing such as grinding, spraying or laser engraving on the housing as required to form the housing of the electronic device.
[0094] Example 4
[0095] The difference between this embodiment and embodiment 1 is that the aspect ratio of the selected aramid fiber is different. The aspect ratio of the selected aramid fiber in this embodiment is 15:1.
[0096] Example 5
[0097] The difference between this embodiment and embodiment 1 is that the aspect ratio of the selected aramid fiber is different. The aspect ratio of the selected aramid fiber in this embodiment is 20:1.
[0098] Example 6
[0099] The difference between this embodiment and embodiment 4 is that the particle size of the aramid fiber selected is different. The particle size of the aramid fiber selected in this embodiment is 15 microns.
[0100] Example 7
[0101] The difference between this embodiment and embodiment 4 is that the particle size of the aramid fiber selected is different. The particle size of the aramid fiber selected in this embodiment is 20 microns.
[0102] Example 8
[0103] The difference between this embodiment and embodiment 4 is that the aramid fiber selected is subjected to modification. The aramid fiber selected in this embodiment is subjected to the following modification steps:
[0104] The aramid fiber was placed in a 1.5 mg / ml polydopamine buffer solution and stirred for 22 hours; the buffer used in the polydopamine buffer solution was a 1 mol / L tris(hydroxymethyl)aminomethane hydrochloride buffer solution, and the pH value of the buffer solution was 8.5. The aramid fiber with the polydopamine coating was then dried at room temperature for 24 hours and then immersed in a 1.5 wt% γ-aminopropyltriethoxysilane (silane coupling agent KH550) solution for 22 hours to obtain a modified aramid fiber.
[0105] Example 9
[0106] The difference between this embodiment and embodiment 8 is that the details of the modification of the aramid fiber are different. In this embodiment, the aramid fiber is selected to undergo the following modification steps:
[0107] The aramid fiber was placed in a 2.0 mg / ml polydopamine buffer solution and stirred for 24 hours; the buffer used in the polydopamine buffer solution was a 1 mol / L tris(hydroxymethyl)aminomethane hydrochloride buffer solution, and the pH value of the buffer solution was 8.5. The aramid fiber with the polydopamine coating was then dried at room temperature for 24 hours and then immersed in a 2.0 wt% γ-aminopropyltriethoxysilane (silane coupling agent KH550) solution for 24 hours to obtain a modified aramid fiber.
[0108] Example 10
[0109] The difference between this embodiment and embodiment 8 is that the details of the modification of the aramid fiber are different. In this embodiment, the aramid fiber is selected to undergo the following modification steps:
[0110] The aramid fiber was placed in a 3.5 mg / ml polydopamine buffer solution and stirred for 26 hours; the buffer used in the polydopamine buffer solution was a 1 mol / L tris(hydroxymethyl)aminomethane hydrochloride buffer solution, and the pH value of the buffer solution was 8.5. The aramid fiber with the polydopamine coating was then dried at room temperature for 24 hours and then immersed in a 2.5 wt% γ-aminopropyltriethoxysilane (silane coupling agent KH550) solution for 26 hours to obtain a modified aramid fiber.
[0111] Comparative Example 1
[0112] A commercially available power bank is selected with a size and weight similar to that of the power bank shell prepared in the embodiment.
[0113] Comparative Example 2
[0114] The difference between this comparative example and Example 1 is that the ratio of the formula of this comparative example and Example 1 is different.
[0115] The raw materials and proportions of this comparative example are as follows:
[0116] 88 parts of PC, 18 parts of aramid fiber, 3 parts of TPU, 0.6 parts of organic phosphate heat stabilizer, 0.1 parts of hindered phenol antioxidant, and 1 part of stearate lubricant.
[0117] Comparative Example 3
[0118] The difference between this comparative example and Example 1 is that the ratio of the formula of this comparative example and Example 1 is different.
[0119] The raw materials and proportions of this comparative example are as follows:
[0120] 65 parts of PC, 8 parts of aramid fiber, 15 parts of TPU, 0.1 parts of organic phosphate heat stabilizer, 0.5 parts of hindered phenol antioxidant, and 1 part of stearate lubricant.
[0121] Comparative Example 4
[0122] The difference between this comparative example and Example 4 is that the aspect ratio of the selected aramid fiber is different. The aspect ratio of the selected aramid fiber in this comparative example is 25:1.
[0123] Comparative Example 5
[0124] The difference between this comparative example and Example 4 is that the particle size of the aramid fiber selected is different. The particle size of the aramid fiber selected in this comparative example is 25 microns.
[0125] Comparative Example 6
[0126] The difference between this comparative example and Example 4 is that the particle size of the aramid fiber selected is different. The particle size of the aramid fiber selected in this comparative example is 8 microns.
[0127] Comparative Example 7
[0128] The difference between this comparative example and Example 9 is that the aramid fiber modification treatment steps are different. The aramid fiber selected in this comparative example is subjected to the following modification steps:
[0129] The aramid fiber was placed in a 2.0 mg / ml polydopamine buffer solution and stirred for 24 hours; the buffer used in the polydopamine buffer solution was 1 mol / L tris(hydroxymethyl)aminomethane hydrochloride) buffer, and the pH value of the buffer was 8.5. The aramid fiber with the polydopamine coating was then dried at room temperature for 24 hours to obtain the modified aramid fiber.
[0130] Comparative Example 8
[0131] The difference between this example and Example 9 is that the details of the modification treatment of the aramid fiber are different. The aramid fiber selected in this comparative example is subjected to the following modification steps:
[0132] The aramid fiber was placed in a 1.0 mg / ml polydopamine buffer solution and stirred for 24 hours; the buffer used in the polydopamine buffer solution was a 1 mol / L tris(hydroxymethyl)aminomethane hydrochloride buffer solution, and the pH value of the buffer solution was 8.5. The aramid fiber with the polydopamine coating was then dried at room temperature for 24 hours and then immersed in a 2.0 wt% γ-aminopropyltriethoxysilane (silane coupling agent KH550) solution for 24 hours to obtain a modified aramid fiber.
[0133] Comparative Example 9
[0134] The difference between this comparative example and Example 1 is that an equal amount of PC is used to replace TPU in this comparative example.
[0135] Test and Inspection
[0136] The electronic device shells prepared in Examples 1-10 all meet the requirements of thermal conductivity greater than 1.7 W / m*K for electronic devices and flame retardancy reaching V-0 level. The weight of the power bank shells prepared in Examples 1-10 is nearly 10%-20% lighter than that of the power bank shells of the same size in Comparative Example 1.
[0137] The charger shells prepared in Examples 1-10 and Comparative Examples 1-9 were subjected to performance tests to further verify the excellent performance of the electronic device shells prepared by the formulation and preparation process of the present invention. Specifically, the performance tests include tensile strength, flexural strength, flexural modulus, roller drop, impact strength, weather resistance impact strength retention rate, and moisture and heat resistance impact strength retention rate. The methods for each effect test are as follows:
[0138] Tensile strength (measures the maximum force that an electronic device casing can withstand when subjected to tension, reflecting the strength and durability of the electronic device casing): ISO527, tensile speed 5mm / min.
[0139] Bending strength (measures the stiffness that the electronic device casing can withstand when bending, reflecting the deformation resistance of the electronic device casing): ISO178:2019, bending speed 2mm / min.
[0140] Drum drop test: The wireless charger shell is made by injection molding and assembled into a product (the wireless charging function electronic components are already installed in the product). After being stored at 23°C for 12 hours, it is freely dropped from a height of 50 cm on the surface of the product for 300 consecutive times. If no cracks are observed, it is considered to have passed.
[0141] Impact strength test (testing the performance of electronic equipment housing under sudden impact, ensuring the impact resistance in daily use and the attenuation of the impact resistance of the housing material after long-term exposure to harsh environments (such as high temperature, high humidity, temperature difference changes, etc.)
[0142] 1. Notched impact strength, ISO180, at 23°C.
[0143] 2. The impact strength retention rate of moisture and heat resistance refers to the percentage of the notched impact strength tested at 85% humidity, 85°C, and 1000h to the notched impact strength tested at 23°C.
[0144] 3. The weather resistance impact strength retention rate refers to the percentage of the notched impact strength tested in ASTMG155-13 cycle 1 and after UV aging to the notched impact strength tested at 23°C.
[0145] The test results are as follows:
[0146] Table 1 Performance test table of electronic equipment housing prepared by Examples 1-10 and Comparative Examples 1-8
[0147]
[0148]
[0149] Combined with the above test results, the electronic device housing prepared by the embodiment of the present invention performs well in terms of drop resistance. From high tensile strength and bending strength to notched impact performance, and the ability to pass the drum drop test, these factors together show that the electronic device housing prepared by using the raw materials of the present invention and the proportions within the limited range of the present invention has a strong drop resistance system, so that the electronic device can effectively resist various accidental drops and impacts in daily use.
[0150] Specifically, further analysis is performed in combination with the test data in Examples 8-10 and Example 4 and Table 1. The aramid fiber has a smooth surface and fewer active groups. It has no way to fully exert its tensile strength and crack blocking and toughening effects during the blending process with the polymer resin. The modified aramid fiber, the polydopamine (PDA) coating can provide abundant hydroxyl groups, which can serve as reactive sites and covalently bond with the KH550 molecules. One end of KH550 can react with the hydroxyl groups of the PDA coating, while the other end forms a stable chemical bond with the PC resin. These covalent bonds enhance the interfacial bonding between the aramid fiber and the PC resin, thereby improving the mechanical properties and stability of the overall material, thereby showing excellent anti-fall performance.
[0151] Combining comparative examples 7-8, embodiments 8-10 and the test data in Table 1, it can be obtained that when the modification method of the present invention is used, the aramid fiber has good mechanical properties in the system in a macroscopic manner, wherein the modification effect of using a 2.0 mg / ml polydopamine buffer solution and a 2.0 wt% γ-aminopropyltriethoxysilane (silane coupling agent KH550) solution is good. Not only does the tensile strength and flexural strength show excellent performance, with a tensile strength of 125 MPa and a flexural strength of 200 MPa, but also after exposing the electronic equipment to high temperature, high humidity, large temperature difference and other environments for a long time and the reverse impact strength test, it still has a high retention rate of about 95%.
[0152] Combining Comparative Examples 4-6 with the embodiment and the test data in Table 1, it can be seen that the aspect ratio of the aramid fiber and the selection of the particle size in the entire system have an important influence on the mechanical strength of the formed electronic device housing.
[0153] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. An anti-fall housing for an electronic device, characterized in that: The following components are included by weight: 70-85 parts of high molecular polymer substrate; 10-15 parts of reinforcing filler; 5-10 parts of impact modifier; Heat stabilizer 0.1-0.5 parts; Antioxidant 0.1-0.5 parts; 0.5-1 part of lubricant.
2. The drop-resistant housing of an electronic device according to claim 1, characterized in that: The high molecular polymer substrate is PC; the impact modifier is TPU.
3. The drop-resistant housing for electronic equipment according to claim 1, characterized in that: The antioxidant is a hindered phenol antioxidant; the heat stabilizer is an organic phosphate heat stabilizer; and the lubricant is a stearate lubricant.
4. The drop-resistant housing for electronic equipment according to claim 1, characterized in that: The reinforcing filler is aramid fiber.
5. The drop-resistant housing of an electronic device according to claim 4, characterized in that: The aspect ratio of the aramid fiber is between 10:1 and 20:
1.
6. The drop-resistant housing of an electronic device according to claim 4, characterized in that: The average particle size of the aramid fiber is between 10 and 20 microns.
7. The drop-resistant housing for electronic equipment according to claim 4, characterized in that: The aramid fiber needs to be modified, and the modification step includes placing the aramid fiber in a 1.5-3.5 mg / ml polydopamine buffer solution and continuously stirring the reaction for 22-26 hours; then drying the aramid fiber coated with polydopamine at room temperature for 24 hours, and then immersing it in a 1.5-2.5wt% γ-aminopropyltriethoxysilane solution for 22-26 hours to obtain modified aramid fiber.
8. The drop-resistant housing of an electronic device according to claim 7, characterized in that: The buffer used in the polydopamine buffer solution is 1 mol / L tris(hydroxymethyl)aminomethane hydrochloride buffer, and the pH value of the buffer is 8.
5.
9. A method for preparing a drop-resistant casing for an electronic device according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step S1: drying the polymer substrate and reinforcing filler, and keeping the humidity of the polymer substrate and reinforcing filler after drying less than 0.04%; Step S2: After the drying process in step S1 is completed, the high molecular polymer substrate, reinforcing filler and impact modifier, thermal stabilizer, antioxidant, and lubricant are mixed in proportion, and then melt-mixed by a twin-screw extruder to ensure that the components are evenly dispersed; Step S3: using an injection molding process to inject molten plastic into a mold to form the shape of an electronic device housing; Step S4: Perform post-processing such as grinding, spraying or laser engraving on the shell as needed.
10. The method for preparing a drop-resistant casing for an electronic device according to claim 9, characterized in that: In step S1, the drying process is carried out under the following conditions: maintaining the temperature within the range of 90° C. to 110° C. and continuing the drying process for 2 to 4 hours.
Citation Information
Patent Citations
High-gloss long-acting solvent-resistant polycarbonate material and preparation method thereof
CN111117197A
Method for reinforcing wood powder / polyolefin composite material by utilizing surface-treated continuous aramid fibers
CN112322064A
Aramid fiber reinforced PC / ABS alloy material special for automobile inner door handle and preparation method of aramid fiber reinforced PC / ABS alloy material
CN115960448A
Composite recyclable ton bag material and preparation method thereof
CN117445512A
Reinforced flame-retardant PC / ABS alloy material and preparation method thereof
CN117986833A
